Gait Parameters and Peripheral Neuropathy in Patients With Diabetes: A Meta-Analysis - Wang, Zhenchao; Peng, Si; Zhang, Honghong; Sun, Hong; Hu, Ji (Frontiers in endocrinology (Lausanne), 2022)
To investigate the relationship between diabetic peripheral neuropathy (DPN) and gait abnormality in diabetic patients. Related research concerning the gait of diabetic patients with and without DPN was collected and analyzed by searching PubMed, Embase, and Web of Science. Statistical analysis was performed by using RevMan 5.3 software. Twenty-one studies were included in this meta-analysis, consisting of 499 diabetic neuropathy patients and 467 diabetes controls without neuropathy. Meta-analysis results showed lower gait velocity, shorter stride length, longer stride time, longer stance time, and higher maximum knee extension moment in the DPN group, compared with their counterparts. Among diabetic patients, those complicated with DPN possess lower gait velocity, shorter stride length, longer stride time, longer stance time, and higher maximum knee extension moment.